Pelatihan Pengakuan, Pengukuran, dan Pencatatan Aset pada Masyarakat Pengrajin Songket di Desa Muara Penimbung Ilir - Gozali, Efva Octavina Donata; Raneo, Agung Putra; Hamzah, Ruth Samantha; Listya, Anisa (Universitas katolik Musi Charitas, 2021)
This community service aims to provide knowledge about the recognition, measurement, and recording of assets. This activity was addressed to community of songket business in Muara Penimbung Ilir, Ogan Ilir Regency, South Sumatra Province, Indonesia. Lecture and discussion as well as simulation and mentoring were used as the methods. This activity had been conducted for three months, started on August until October 2021, while the visits for training were given three times. The main problem faced by songket business is capital constraint since they have poor knowledge about managing internal resources, namely assets. The results of this community service indicate that after the training had been given, the songket businessman is equipped with knowledge of asset recognition, measurement and recording.